2019
DOI: 10.1016/s1473-3099(18)30547-4
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of oral antibiotic formulations for young children according to the WHO Access, Watch, Reserve (AWaRe) antibiotic groups: an analysis of sales data from 70 middle-income and high-income countries

Abstract: Background: The 2017 WHO model list of essential medicines for children grouping of antibiotics (Access, Watch, Reserve: AWaRe) provides an opportunity to review country-level antibiotic consumption and potential for stewardship. We aimed to review 2015 levels of oral antibiotic consumption by young children, globally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
172
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(181 citation statements)
references
References 55 publications
(73 reference statements)
6
172
1
2
Order By: Relevance
“…Regular monitoring of prescribing activities for patients with URTIs in ambulatory care using both quantitative and qualitative research methods -helped by IT systems and mobile technologies. This can include accountability systems for prescribers where they have to justify the need for an antibiotic for patients with URTIs as well as the antibiotic selected (building on restrictions for certain antibiotics in a number of countries as well as the WHO Access, Watch, Reserve -AwaRe -antibiotic groupings 40,71,387,388 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regular monitoring of prescribing activities for patients with URTIs in ambulatory care using both quantitative and qualitative research methods -helped by IT systems and mobile technologies. This can include accountability systems for prescribers where they have to justify the need for an antibiotic for patients with URTIs as well as the antibiotic selected (building on restrictions for certain antibiotics in a number of countries as well as the WHO Access, Watch, Reserve -AwaRe -antibiotic groupings 40,71,387,388 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have used pharmaceutical sales data, which reflect the antibiotic consumption of whole countries rather than individuals or communities. 5,30,31 Nevertheless, despite the different data sources used, the proportion of prescribed antibiotics that were access antibiotics was broadly similar across paediatric studies. One international study found that 76.0% of all antibiotics used were access antibiotics (compared with 72.4% in our study) and 30.7% were amoxicillin (compared with 33.9% in our study).…”
Section: Researchmentioning
confidence: 99%
“…Like many LMIC settings, ensuring appropriate access to antibiotics, while also avoiding excess use, is a major challenge in this context [60][61][62]. Bangladesh has a high degree of antibiotic resistance, posing a global and regional threat, due to misuse of antibiotics in healthcare and agricultural sectors [63].…”
Section: Plos Onementioning
confidence: 99%